การศึกษาปัจจัยความพึงพอใจของลูกค้าเพื่อพัฒนาการดำเนินงานของผู้รับเหมาก่อสร้าง - ณ พัทลุง ชวิน; จารุชัยมนตรี ทยากร (NAJUA: Architecture, Design and Built Environment, 2017)
การศึกษานี้มีวัตถุประสงค์ เพื่อหาแนวทางพัฒนาการดำเนินงานของผูรั้บเหมาก่อสร้างบ้านเดี่ยว มูลค่า 2.5-5 ล้านบาท ในเขตกรุงเทพมหานคร จากปัจจัยความพึงพอใจของลูกค้าผ่านเทคนิคการแปลงหน้าที่เชิงคุณภาพ (Quality Function Deployment, QFD) ซึ่งเป็นเครื่องมือสำหรับพัฒนาคุณภาพของผลิตภัณฑ์ หรือคุณภาพการบริการขององค์กร เพื่อตอบสนองความต้องการของลูกค้า จนเกิดความพึงพอใจ การศึกษาประกอบด้วยการหาปัจจัยความพึงพอใจของลูกค้าในงานก่อสร้าง การสร้างแบบสอบถามเพื่อเก็บข้อมูลความถี่จากกลุ่มตัวอย่าง กระบวนการเทคนิคการแปลงหน้าที่เชิงคุณภาพ และการพัฒนาบ้านแห่งคุณภาพ (House of quality) ซึ่งแสดงความสัมพันธ์ของปัจจัยความพึงพอใจ สัดส่วนการปรับปรุงโดยเทียบระหว่างประสบการณ์กับความคาดหวังของลูกค้าที่มีต่อการดำเนินงานของผู้รับเหมา ข้อมูลเชิงเทคนิค ค่าลำดับความสำคัญของแนวทางการพัฒนาการดำเนินงานที่สามารถสร้างความพึงพอใจให้แก่ลูกค้าได้สูงสุดจากผลการศึกษาพบว่า การดำเนินงานของผู้รับเหมายังไม่สามารถตอบสนองความต้องการของลูกค้า จนทำให้เกิดความพึงพอใจได้ โดยเฉพาะปัจจัยความพึงพอใจในกลุ่มการตรวจสอบดูแล ควบคุมงาน และ ปัจจัยการประกันคุณภาพ การส่งมอบงานซึ่งจำเป็นต้องมีการพัฒนาก่อนเป็นลำดับต้นๆ A Study of Customer Satisfaction for Developing Construction Contractors’ Work Chawin Na Pattalung Master of Science Program in Construction Management, Faculty of Architecture, Silpakorn University Tayagorn Charuchaimontrin Faculty of Architecture, Silpakorn University This study aims to develop the contractors’ work from customer satisfaction for detached houses in Bangkok that have value between 2.5-5 million baht. Using quality function deployment (QFD) technique, qualitative tool for production development or organization service quality, to respond the customers’ need that affect the customer satisfaction. The process of the study is searching for customer satisfaction factors in construction work, setting up the questionnaire to record the frequency data from representative sample, evaluating analysis with quality function deployment technique and house of quality development. The criteria is the relationship of satisfaction factors, improvement ratio that compare between customers’ experience and expectation for contractors’ work, technical requirement and the hierarchy of working development process to maximize customer satisfaction. The study result shows that contractors’ work does not have enough responsibility to satisfy customer, especially for construction management, quality guarantee and delivery. Almost there are urgent necessary to be developed.